2015
DOI: 10.4049/jimmunol.1402752
|View full text |Cite
|
Sign up to set email alerts
|

Activation of TAK1 by Chemotactic and Growth Factors, and Its Impact on Human Neutrophil Signaling and Functional Responses

Abstract: The MAP3 kinase, TAK1, is known to act upstream of IKK and MAPK cascades in several cell types, and is typically activated in response to cytokines (e.g., TNF, IL-1) and TLR ligands. In this article, we report that in human neutrophils, TAK1 can also be activated by different classes of inflammatory stimuli, namely, chemoattractants and growth factors. After stimulation with such agents, TAK1 becomes rapidly and transiently activated. Blocking TAK1 kinase activity with a highly selective inhibitor (5z-7-oxozea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 51 publications
4
17
0
Order By: Relevance
“…By contrast, inhibition of Src tyrosine kinases consistently failed to interfere with NETosis. For physiological stimuli such as TNFα, fMLP, or GM-CSF, our data are consistent with our previous findings, which showed that they can all signal through the TAK1-MEK or TAK1-p38 axes in neutrophils ( 43 , 44 ). Conversely, PMA does not activate TAK1 in these cells (our unpublished data), and accordingly, TAK1 inhibition had no significant effect on PMA-elicited NETosis.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, inhibition of Src tyrosine kinases consistently failed to interfere with NETosis. For physiological stimuli such as TNFα, fMLP, or GM-CSF, our data are consistent with our previous findings, which showed that they can all signal through the TAK1-MEK or TAK1-p38 axes in neutrophils ( 43 , 44 ). Conversely, PMA does not activate TAK1 in these cells (our unpublished data), and accordingly, TAK1 inhibition had no significant effect on PMA-elicited NETosis.…”
Section: Discussionsupporting
confidence: 92%
“…We have shown previously that the p38 MAPK, MEK/ERK, and PI3K/Akt cascades are controlled by the MAP3K, TAK1, in human neutrophils exposed to various physiological stimuli (24,25,32,33). We therefore verified whether this is also the case in response to MSU crystals.…”
Section: Signaling Cascades That Are Rapidly Elicited By Msusupporting
confidence: 64%
“…By comparison, our data represents the first demonstration that ERK and Akt Ser473 can also be activated by MSU. Thus, the kinases activated by MSU are essentially the same as those mobilized by several physiological neutrophil agonists (23,25,26,33,39,40). Morevoer, we found that the MSU-elicited phosphorylation of p38 MAPK, ERK, and Akt occurs downstream of TAK1 and Syk, much like it does in response to several classical neutrophil stimuli (24,33).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…More recently, we also found that FcγRIIIb induced a robust activation of ERK and also of the transcription factor Elk-1 ( 17 ), but we could not identify the molecule responsible for ERK activation. Similarly, others have reported that, in human neutrophils, TAK1 acted upstream of MEK (ERK kinase) and ERK signaling pathway ( 18 , 19 ). Thus, in this report, we explored the possibility that TAK1 is functionally coupled to FcγRIIIb leading to NETosis via ERK activation.…”
Section: Introductionmentioning
confidence: 75%